Prevalence and determinants of malnutrition among under-five children in Southwest, Nigeria - Ogunniyi, Kayode; Oyebade, Akin; Atolagbe, James (International Journal Of Community Medicine And Public Health, 2023)
Background: Malnutrition refers to deficiencies or excesses in nutrient intake, imbalance of essential nutrients or impaired nutrient utilization. Around 45% of deaths among children under-five years are linked to undernutrition which mostly occurs in low and middle-income countries. This study aimed to determine the prevalence and assess determinants of undernutrition among under five children in South West of Nigeria. Methods: A cross sectional study design, multi stage sampling method and sample size of 327 under-five children were utilized for the study. Results: The prevalence of underweight was 30.6%, overweight was 2.1% and normal weight for age nutritional status was 67.3%. More males (19.6%) than females (11%) accounted for prevalence of underweight. Majority (25.7%) of underweight under five years children were in the age group of 0-11 months, 4.6% in age group 12-29 months and 0.3% in age group 30-39 months. This study revealed statistically significant association between underweight nutritional status and child’s sex (male, p=0.006), knowledge of importance of vaccination against vaccine preventable diseases (VPD) on nutrition (p=0.01) and presence of clinical signs of malnutrition (hair changes p=0.003, swelling of legs 0.006 and pallor of mucus membrane p=0.006). Conclusions: There is need to implement urgent nutritional intervention to reduce the high prevalence of malnutrition in Ede North LGA. Food security should be improved and high levels of inflation should be reduced to enable mothers to have access to food items. Health education should be intensified to educate mothers on prevention of early malnutrition and importance of vaccination against VPDs.